2006
DOI: 10.1002/gcc.20389
|View full text |Cite
|
Sign up to set email alerts
|

Common fragile site FRA11G and rare fragile site FRA11B at 11q23.3 encompass distinct genomic regions

Abstract: Fragile sites are specific genomic loci that are particularly prone to chromosomal breakage. Based on their incidence in the human population, they are divided into rare fragile sites occurring in less than 5% of all individuals and common fragile sites being a constitutional feature of the genome of probably all individuals. In this study, cloning of unstable DNA sequences, which have been previously genetically tagged with a marker gene, was the basis for defining the genomic localization of the common fragi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 45 publications
(62 reference statements)
0
12
0
Order By: Relevance
“…We were able to find high-resolution genomic coordinates of 18 autosomal cloned aCFS either using BAC accession numbers (Ciullo et al 2002;Fechter et al 2007;Reshmi et al 2007;Bosco et al 2010;Pelliccia et al 2010;Blumrich et al 2011) or data collected by Ruiz-Herrera and colleagues (Ruiz-Herrera et al 2006). Among these,14 (FRA2C,FRA2G,FRA2H,FRA3B,FRA4F,FRA6E,FRA6F,FRA7B,FRA7G,FRA7H,FRA9E,FRA11F,FRA11G, and FRA13A) overlapped with aCFSs cytogenetically defined by Mrasek and colleagues (Mrasek et al 2010), while high-resolution coordinates for the remaining four (FRA1E, FRA7E, FRA7I, and FRA16D) did not overlap with their cytogenetic coordinates (Supplemental Table S8).…”
Section: Validation In Cloned Acfssmentioning
confidence: 99%
See 1 more Smart Citation
“…We were able to find high-resolution genomic coordinates of 18 autosomal cloned aCFS either using BAC accession numbers (Ciullo et al 2002;Fechter et al 2007;Reshmi et al 2007;Bosco et al 2010;Pelliccia et al 2010;Blumrich et al 2011) or data collected by Ruiz-Herrera and colleagues (Ruiz-Herrera et al 2006). Among these,14 (FRA2C,FRA2G,FRA2H,FRA3B,FRA4F,FRA6E,FRA6F,FRA7B,FRA7G,FRA7H,FRA9E,FRA11F,FRA11G, and FRA13A) overlapped with aCFSs cytogenetically defined by Mrasek and colleagues (Mrasek et al 2010), while high-resolution coordinates for the remaining four (FRA1E, FRA7E, FRA7I, and FRA16D) did not overlap with their cytogenetic coordinates (Supplemental Table S8).…”
Section: Validation In Cloned Acfssmentioning
confidence: 99%
“…Eighteen autosomal aCFSs mapped by fluorescence probes (i.e., "cloned") (Ciullo et al 2002;Ruiz-Herrera et al 2006;Fechter et al 2007;Reshmi et al 2007;Bosco et al 2010;Pelliccia et al 2010;Blumrich et al 2011) were studied. For analysis, we intersected their cloned and cytogenetically defined coordinates.…”
Section: Cloned Acfssmentioning
confidence: 99%
“…FRA11G is a common fragile site located on 11q23.3, rendering this region susceptible to frequent genomic instability [19]. Deletion of the H2A histone family, member X (H2AFX) gene on chromosome 11q23.3 has been associated with genomic instability and tumorigenesis; recently, Srivastava et al found that deletion of H2AFX was associated with high-grade tumors and suggested that deletion of H2AFX may be an early event, leading to uncontrolled cellular proliferation and initiation of tumor development [20].…”
Section: Discussionmentioning
confidence: 99%
“…For 19 of these, namely FRA2G, FRA3B, FRA6F, FRA6E, FRA7E, FRA7G, FRA7H, FRA7I, FRA8C, FRA9E, FRA16D, FRAXB (Schwartz et al, 2006), FRA13A (Savelyeva et al, 2006a), FRA1E (Hormozian et al, 2006), FRA11E (Bester et al, 2006), FRA11F (Reshmi et al, 2007), FRA11G (Fechter et al, 2007a), FRA1H (Curatolo et al, 2007), and FRA18C (Debacker et al, 2007) DNA sequences have been determined and characterized at the molecular level. However, the exact number of common fragile sites appears to be even larger than those identified by classical cytogenetic analysis.…”
Section: Introductionmentioning
confidence: 97%